Pengaruh Model Pembelajaran Scramble terhadap Minat dan Hasil Belajar Matematika di SD Negeri Nanggulan Maguwoharjo - Susi Setia Ningsih Ningsih; Imam Machali (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2022)
This study aims to determine the influence of the scramble learning model on the interest and learning outcomes of fourth grade mathematics at SDN Nanggulan. This type of research is a Quasi Experiment with a quantitative approach. Data collection techniques using questionnaires, tests, interviews and documentation. Hypothesis testing using Multivariate Of Analysis Variance (MANOVA).To test the data analysis is done by using the SPSS application. The results showed that 1) There is an influence of the scramble learning model on the interest in learning mathematics of fourth grade students with the results of the univariate test analysis, namely the sig value. 0.037 < 0.05 and it can be said that Ha is accepted. 2) There is an influence of the scramble learning model on the fourth grade students' mathematics learning outcomes with the results of the univariate test analysis, namely the value of sig. 0.038 < 0.05 and it can be said that Ha is accepted. 3) There is an effect of the Scramble learning model on the interest and learning outcomes of fourth grade students in mathematics. This is based on the results of the multivariate test analysis, namely the results of the Pillai's Trace, Wilks' Lambda, Hotelling's Trace and Roy's Largest Root tests have a sig value. of 0.040 < 0.05 and it can be said that Ha is accepted.